Avaliação da atividade antidiarreica em camundongos e antimicrobiana in vitro do extrato bruto das cascas de fruto de Pouteria caimito (Ruiz e Pavon) Radlk - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Introduction: Pouteria caimito is a native Amazonian fruit, popularly known as "abiu", "caimito", "caimo" and "cauje" that belongs to the Sapotaceae family. It has a wide popular use to alleviate diarrhea, cough, fever and inflammation, among other purposes, however, few reports in the scientific literature point to its constitution and biological activity. Objectives: The objective of this study was to evaluate the antidiarrheal and antimicrobial activity of Pouteria caimito fruit peel extract. Methodology: The antidiarrheal activity was evaluated in mice, using modulation models of normal defecation, diarrhea induced by cathartic agent and stimulation of the intestinal transit. Antimicrobial activity was analyzed against strains of gram-positive and negative bacteria: E. coli, S. epidermidis, S. aureus, Klebsiella pneumonie, E. faecalis and Salmonella tiphy by determining the minimum inhibitory concentration by microdilution methods. Results and discussion: The results of this study showed that there was no antidiarrheal action in the experimental models and that methanolic extract of P. caimito (MEPC) can positively modulate normal defecation. Regarding the antimicrobial activity, the crude extract and the ethyl acetate fraction presented a satisfactory action against most of the strains evaluated except for Enterococcus faecalis and Salmonella tiphy. Conclusions: The research concluded that MEPC did not show significant antidiarrheal activity, more possibly a laxative effect. The extract showed antimicrobial activity as well as the acetate fraction against strains of gram-positive and gram-negative bacteria. The activity of the crude extract was more potent than the results obtained by the use of acetate fractions; the fractions with lower polarity did not present any relevant antimicrobial activity
Keywords: Extrato - Pouteria caimito; Plantas medicinais; Atividade antimicrobiana; Ensaio biológico; CNPQ::CIENCIAS BIOLOGICAS::FARMACOLOGIA::FARMACOLOGIA BIOQUIMICA E MOLECULAR; VALIDAÇÃO QUÍMICA-BIOLÓGICA DE FÁRMACOS DE ORIGEM SINTÉTICA E NATURAL; BIOLOGIA FARMACÊUTICA